Optimizing PEMFC model parameters using ant lion optimizer and dragonfly algorithm: A comparative study - Zainuddin Mat Isa; Norkharziana Mohd Nayan; Mohd Hafiz Arshad; Nor Ashbahani Mohamad Kajaan (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper introduced two optimization algorithms which are Ant Lion Optimizer (ALO) and Dragonfly Algorithm (DA) for extracting the Proton Exchange Membrane Fuel Cell (PEMFC) polarization curve parameters. The results produced by both algorithms are being compared to observe their performance. As a results, the ALO shows great performance compared to DA. Furthermore, these results also being compared with the results of the other reported metaheuristics algorithms. The ALO and DA presented competitive results.